An Efficient Green Procedure for Synthesis of Some Fluorinated Curcumin Analogues Catalyzed by Calcium Oxide under Microwave Irradiation and Its Antibacterial Evaluation - S. Elavarasan; D. Bhakiaraj; T. Elavarasan; M. Gopalakrishnan (Journal of Chemistry)
A series of fluorine substituted curcumin analogues have been synthesized in a cheaper and greener method using calcium oxide as catalyst under microwave irradiation. All the synthesized compounds have been characterized by FT-IR, MS, elemental analysis, and 1H and 13C NMR spectroscopic techniques and screened for antibacterial activities against Staphylococcus aureus, β-Heamolytic streptococcus, Shigella flexneri, Vibrio cholerae, Pseudomonas aeruginosa, and Klebsiella pneumonia. All the synthesized compounds are showing good zone of inhibition against the tested bacterial strains.